Nutritional Knowledge, Practice, and Dietary Habits among school Children and Adolescents - Naeeni, Marjan Manouchehri (Int J Prev Med, 2014)
BACKGROUND: Although nutritional status of children and adolescents is of great concern various interventions and modifications aiming at promotion of healthy eating behaviors have limited impact due to insufficient understanding of dietary habits between different age groups and genders. The aim of this study in not only evaluation of nutritional knowledge, practice, and dietary habits of primary school and junior high school students in Isfahan province, but also this research explore crucial differences regarding gender and living area of the above-mentioned population in Iran. METHODS: This cross-sectional study was conducted on 4700 primary school and junior high school pupils in Isfahan province. Data were collected through standard 24-h recall food frequency questionnaire and researcher-designed questionnaire. Independent t-test was applied for comparison of mean values of total units of consumed food materials. Qualitative variables were compared by using the Chi-square test. Data were analyzed by ACCESS 2010 and SPSS 18 software. RESULTS: Nutritional knowledge of female pupils and junior high school students was higher than their male and elementary school students respectively; still, theses superiorities did not lead to higher practice score. Bread and cereals group received daily intakes in accordance with food and drug administration (FDA) recommendations. Indeed, vegetables, milk, and dairy products, as well as meat daily intakes, were lower than the FDA recommendation, whereas fats, oils, and sugars intakes were higher. In comparison to females, male participants had significantly lower consumption of vegetables and fruits whilst they had a higher intake of carbohydrates, fats, and meats. CONCLUSIONS: Our results showed that adolescents failed to meet sufficient nutritional requirements, and they had an imbalanced diet, which was considerably low in several essential nutrients and high in some food materials.